Knowledge, freedom, and responsibility: A philosophical approach to education in the age of AI - Nhung, Le Thi Thuy; Quoc, Nguyen Anh (Edelweiss Applied Science and Technology, 2025)
The article aims to analyze and redefine the role of education within the context of knowledge globalization, knowledge commercialization, and the rapid development of artificial intelligence (AI). Its primary objective is to critique the trend of standardizing education according to market logic and to propose a humanistic-realist philosophical foundation that views education as a process of cultivating ethical, creative, and socially responsible individuals. The research employs an interdisciplinary approach, integrating human philosophy, critical sociology, and educational science. Based on this foundation, the article applies critical discourse analysis and a transformation model that examines the opposition between pairs such as instinct versus creativity, norms versus freedom, and tools versus subjects to identify paradoxes within the structure of modern education. The findings indicate that contemporary education is heavily influenced by powerful institutions, established norms, and commercialization pressures, which pose risks of human degeneration into what can be described as "biological robots." Nonetheless, if education is restructured around scientific knowledge and human values, it can continue to serve as a vital instrument for liberating individuals and fostering sustainable development. The conclusion emphasizes the importance of restoring education’s core function as a dynamic and living process—where individuals are simultaneously learners, knowledge creators, and moral agents in a constantly changing world.